2013
DOI: 10.1007/s00520-013-1806-7
|View full text |Cite
|
Sign up to set email alerts
|

‘They’re survivors physically but we want them to survive mentally as well’: health care professionals’ views on providing potential late effect information

Abstract: Purpose: The concept of providing personalised care plans for cancer survivors is receiving increasing attention; a recognised element of a care plan is to provide an indication of the risks and consequences of treatment. This paper reports health care professional (HCP) response to providing cancer survivors with information on potential late effects of their cancer treatment.Methods: Eighteen HCPs from five cancer centres and three general practices in the UK completed semi-structured interviews which were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…However, those who were distressed by this information expressed a greater desire for detailed information concerning longterm outcomes. Many oncologists worry that providing information regarding potential future limitations may upset parents, 11,12 and although the results of the current study support this as a legitimate concern, they also suggest that parental distress should not be considered a reason to avoid conversations. Instead, parents who are distressed may need more information, or an opportunity to have continued discussions over time.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, those who were distressed by this information expressed a greater desire for detailed information concerning longterm outcomes. Many oncologists worry that providing information regarding potential future limitations may upset parents, 11,12 and although the results of the current study support this as a legitimate concern, they also suggest that parental distress should not be considered a reason to avoid conversations. Instead, parents who are distressed may need more information, or an opportunity to have continued discussions over time.…”
Section: Discussionmentioning
confidence: 50%
“…The gap between parent communication preferences regarding future limitations and the information they receive may be due in part to provider concerns regarding discussing potential impairment. Providers often hesitate to discuss late effects throughout the cancer care continuum due to concerns about overwhelming patients with information and causing distress . Furthermore, many physicians find it stressful to anticipate and communicate a patient’s likely outcomes, and fear taking away hope .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risks of late effects can be challenging to estimate, let alone convey to families. Many providers are uncomfortable in providing information about late effects of therapy even after treatment completion as they fear taking away hope . Adult oncology providers worry that information about potential late effects of cancer and its treatment will be emotionally upsetting to cancer survivors as it “could have a negative impact on psychological adjustment to life as a cancer survivor and may actually increase the experience of late effects through autosuggestion.” These concerns are likely magnified in the setting of heightened emotions at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many providers are uncomfortable in providing information about late effects of therapy even after treatment completion as they fear taking away hope . Adult oncology providers worry that information about potential late effects of cancer and its treatment will be emotionally upsetting to cancer survivors as it “could have a negative impact on psychological adjustment to life as a cancer survivor and may actually increase the experience of late effects through autosuggestion.” These concerns are likely magnified in the setting of heightened emotions at diagnosis. However, survivors of childhood cancer with unmet late effects information needs are more likely to experience depression, anxiety and inferior mental and physical health related quality of life, and lack of information does not decrease late effect worries, underscoring the potential importance of this information to psychological health.…”
Section: Discussionmentioning
confidence: 99%
“…One of the barriers to awareness is a belief that unnecessarily worrying people with cancer about long-term effects of therapy may cause distress. Evidence suggests that this is not the case (Cox and Faithfull 2013) and is reflected in studies that report satisfaction with information provision in people living with and beyond cancer. People with Hodgkin lymphoma who were assessed for cardiovascular risks and participated in a recall screening and counselling service found that the additional information improved satisfaction scores (Daniëls et al 2014).…”
Section: Indirect Damagementioning
confidence: 99%